THE ROLE OF SCHOOL COMMITTEES IN IMPROVING THE QUALITY OF EDUCATIONAL SERVICES IN ELEMENTARY SCHOOLS THROUGHOUT THE TANAH ABANG SUBDISTRICT, PALI REGENCY - Rastiana Rastiana; Abdullah Idi; Muslim Gani; Ahmad Zainuri (Jurnal Konseling Pendidikan Islam, 2026)
This study aims to analyze the role of School Committees in improving the quality of educational services in public elementary schools across Tanah Abang District, Penukal Abab Lematang Ilir Regency. This qualitative research employed a multiple-case study design involving three public elementary schools. Data were collected through in-depth interviews, limited participant observation, and document analysis. The analysis followed the interactive model of Miles, Huberman, and Saldaña, enriched with pattern matching and cross-case analysis techniques. The findings reveal that the implementation of school committee roles remains largely administrative and symbolic. The advisory function is procedural rather than deliberative; supporting is incidental rather than strategic; controlling is constrained by limited capacity and transparency; and mediating lacks institutionalization. Drawing on public value governance and co-production perspectives, educational service quality requires institutional capacity building, transparency mechanisms, deliberative planning, and participatory evaluation forums. The study proposes an Integrative School Committee–Service Quality Model positioning the committee as a co-producer of educational service quality.